2018
DOI: 10.1124/mol.118.112631
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Expression of Nur77 and Nurr1 Regulates NF-κB–Dependent Inflammatory Signaling in Astrocytes

Abstract: Inflammatory activation of glial cells promotes loss of dopaminergic neurons in Parkinson disease. The transcription factor nuclear factor κB (NF-κB) regulates the expression of multiple neuroinflammatory cytokines and chemokines in activated glial cells that are damaging to neurons. Thus, inhibition of NF-κB signaling in glial cells could be a promising therapeutic strategy for the prevention of neuroinflammatory injury. Nuclear orphan receptors in the NR4A family, including NR4A1 (Nur77) and NR4A2 (Nurr1), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 56 publications
1
41
0
1
Order By: Relevance
“…The observation that exposure to LPS causes alpha-synuclein to adopt a fibrillar form and the specific patterns of alpha-synucleinopathies seen in mice exposed to this form of alpha-synuclein suggests that bacterial exposure may be a driving force in alpha-synucleinopathies. LPS has also been shown to induce expression of chemokines (Leow-Dyke et al, 2012; Honda and Littman, 2016; Popichak et al, 2018; Lee et al, 2019). Recent studies looking at the mechanisms underlying this interaction have identified an important role of the activation of TLR-4 causing the release of chemokines CCL5/RANTES and CXCL1 as well as TNF-alpha and IL-6 (Leow-Dyke et al, 2012; Perez-Pardo et al, 2018b; Figure 1).…”
Section: Alpha-synuclein In the Microbiota-gut-brain Axis: A Role In mentioning
confidence: 99%
“…The observation that exposure to LPS causes alpha-synuclein to adopt a fibrillar form and the specific patterns of alpha-synucleinopathies seen in mice exposed to this form of alpha-synuclein suggests that bacterial exposure may be a driving force in alpha-synucleinopathies. LPS has also been shown to induce expression of chemokines (Leow-Dyke et al, 2012; Honda and Littman, 2016; Popichak et al, 2018; Lee et al, 2019). Recent studies looking at the mechanisms underlying this interaction have identified an important role of the activation of TLR-4 causing the release of chemokines CCL5/RANTES and CXCL1 as well as TNF-alpha and IL-6 (Leow-Dyke et al, 2012; Perez-Pardo et al, 2018b; Figure 1).…”
Section: Alpha-synuclein In the Microbiota-gut-brain Axis: A Role In mentioning
confidence: 99%
“…Limited information is available regarding the role of Nur77 in PD. The recent studies demonstrated that Nur77 was involved in neurodegeneration [16,17]. Abnormalities of Nur77 may induce dopaminergic imbalances in the brain [18].…”
Section: Introductionmentioning
confidence: 99%
“…Within the adult innate immune system and with metabolic disease, Nr4a1 plays an anti-inflammatory role 58,59 . The mechanisms by which Nr4a1 reduces inflammation have been noted to involve p38, NF-kB, and ISG12 depending on the context of disease, biological modeling, and analyses 19,60,61 . In-depth molecular examination suggests p38 counters Nr4a1 in suppressing NF-kB pro-inflammatory signaling 19 .…”
Section: Discussionmentioning
confidence: 99%